2019
DOI: 10.1111/jvh.13070
|View full text |Cite
|
Sign up to set email alerts
|

HBV T1719G mutation reduced HBV replication through mutant Enh II and HBx protein in vitro

Abstract: Summary It was repeatedly reported that the hepatitis B virus (HBV) T1719G mutation was very common and related to progression and malignancy of liver disease. However, its effect on viral replication efficiency remains unclear. In this study, we aimed to evaluate the function and mechanisms of the T1719G mutation on viral replication capacity. Wild‐type and T1719G mutation‐bearing HBV1.2× plasmids were transfected into Huh7 and HepG2 cells, respectively, and HBV total RNA, 3.5 kb RNA and supernatant HBV DNA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…[13][14][15] There are few studies on the monitoring of HBV RNA resistance, and one study showed that patients with YMDD site mutations within 1 year of NAs treatment had significantly higher patients were HBeAg-negative, possibly due to extremely low cccDNA levels or mutations or epigenetic modifications that resulted in inactive cccDNA transcription. 21,22 One study has found that serum HBV RNA sequences are more similar to cccDNA sequences in liver than serum HBV DNA sequences. 23 Another study has also shown that high-throughput sequencing of serum HBV DNA and HBV RNA from HBV and HIV co-infected patients has shown that HBV RNA detects a higher proportion of wild quasispecies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] There are few studies on the monitoring of HBV RNA resistance, and one study showed that patients with YMDD site mutations within 1 year of NAs treatment had significantly higher patients were HBeAg-negative, possibly due to extremely low cccDNA levels or mutations or epigenetic modifications that resulted in inactive cccDNA transcription. 21,22 One study has found that serum HBV RNA sequences are more similar to cccDNA sequences in liver than serum HBV DNA sequences. 23 Another study has also shown that high-throughput sequencing of serum HBV DNA and HBV RNA from HBV and HIV co-infected patients has shown that HBV RNA detects a higher proportion of wild quasispecies.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these patients were HBeAg‐positive and had poor response to NAs antiviral therapy, resulting in insignificant depletion of cccDNA in hepatocytes. In Group 3, serum HBV RNA was not consistently detectable, and most of these patients were HBeAg‐negative, possibly due to extremely low cccDNA levels or mutations or epigenetic modifications that resulted in inactive cccDNA transcription 21,22 …”
Section: Discussionmentioning
confidence: 99%